HUBUNGAN CARING PERAWAT DENGAN TINGKAT KECEMASAN PASIEN PRE OPERATIF DI RSUD.ALIMUDIN UMAR LIWA KABUPATEN LAMPUNG BARAT - Eka Yudha Chrisanto; Wenny Nopianti (Universitas Malahayati Lampung, 2020)
ABSTRACT : Relationship Between Caring Nurses And The Level Anxiety Of Preoperative Patients In General Hospital Alimuddin Umar Liwa West Lampung Regency In 2019 Introduction: Actions of operations in Indonesia in 2012 reached 1.2 million. The 11th urinary possession surgery of the first 50 hospital treatments in Indonesia, which was estimated at 32%, was approved as a procedure for laparotomy. The number of abdominal surgical cases in Lampung Province in 2017 was (28.95%) and increased in 2018 by (32.45).Purpose: the relationship between caring nurses and the level of anxiety of preoperative patients in RSUD. Alimuddin Umar Liwa West Lampung Regency in 2019MethodS: Type of quantitative research, with analytic research design and cross sectional analytic. The population of all preoperative patients in 2018 was 361 people. And a sample of 138 people with purposive sampling technique. Data collection using questionnaire sheets and statistical tests used are Chi-Square statistical tests.Results: The frequency distribution of the characteristics of preoperative patients, mostly after respondents aged 20-35 years as many as 28 respondents (44.45%), female sex as many as 81 respondents (58.69%), junior high school education as many as 58 respondents (42 , 02%). Caring frequency distribution of nurses in pre-operative patients, with a poor category of 66 respondents (47.8%). High frequency distribution in preoperative patients, with the questionable category as many as 79 respondents (57.2%).Conclusion: There is a relationship between caring nurses and the patient's difficulty level preoperatively. The results of the analysis were obtained (p-value 0,000 α 0,05). OR: 21,914. Health workers are expected to provide special care to treat patients before further surgery is needed in psychological preparation, helping patients in handling adaptive coping, and helping families to carry out their functions in providing support so patients can be responded to. Keywords : Caring Nurses, Level Of Anxiety INTISARI : HUBUNGAN CARING PERAWAT DENGAN TINGKAT KECEMASAN PASIEN PRE OPERATIF DI RSUD.ALIMUDIN UMAR LIWA KABUPATEN LAMPUNG BARAT Pendahuluan: Tindakan operasi di Indonesia pada tahun 2012 mencapai 1,2 juta jiwa. Tindakan bedah menempati ururan ke-11 dari 50 pertama penanganan pola penyakit di rumah sakit di Indonesia yang diperkirakan 32% diantaranya merupakan tindakan bedah laparatomi. Jumlah kasus bedah abdomen di Provinsi Lampung pada tahun 2017 sebesar (28,95%) dan meningkat pada tahun 2018 sebesar (32,45).Tujuan: hubungan caring perawat dengan tingkat kecemasan pasien pre operatif di RSUD. Alimuddin Umar Liwa Kabupaten Lampung Barat Tahun 2019Metode: Jenis penelitian kuantitatif, dengan rancangan penelitian analitik dan pendekatan cross sectional. Populasi seluruh seluruh pasien pre operatif pada tahun 2018 sebanyak 361 orang. Dan sampel sebanyak 138 orang dengan teknik purposive Sampling. Pengumpulan data menggunakan lembar kuesioner dan Uji statistik yang digunakan adalah uji statistik Chi-Square.Hasil Penelitian: Distribusi frekuensi karakteristik responden pasien pre operatif, sebagian besar usai responden adalah usia 20-35 tahun sebanyak 28 responden (44,45%), jenis kelamin perempuan sebanyak 81 responden (58,69%), pendidikan SMP sebanyak 58 responden (42,02%). Distribusi frekuensi caring perawat pada pasien pre operatif, dengan kategori kurang baik sebanyak 66 responden (47,8%).Distribusi frekuensi tingkat kecemasan pada pasien pre operatif, dengan kategori mengalami kecemasan sebanyak 79 responden (57,2%). Kesimpulan: Ada hubungan caring perawat dengan tingkat kecemasan pasien pre operatif. Hasil analisis diperoleh (p-value 0,000 α 0,05). nilai OR: 21,914. Diharapkan petugas kesehatan memberikan asuhan keperawatan khususnya dalam melakukan caring perawat kepada pasien pre operasi lebih ditingkatkan terutama pada persiapan psikologis, membantu pasien mengarahkan mekanisme koping yang adaptif, dan membantu keluarga untuk menjalankan fungsinya dalam memberi dukungan agar tingkat kecemasan pasien menjadi berkurang. Kata Kunci : Caring Perawat, Kecemasan